2009
DOI: 10.15298/rusjtheriol.08.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Circadian activity rhythms of dwarf hamsters (Phodopus spp.) under laboratory and semi-natural conditions

Abstract: The hamsters of the genus Phodopus (P. campbelli, P. sungorus, P. roborovskii) inhabit different ecosystems facing them with different environmental challenges. This should have behavioural and physiological consequences, manifested genetically. Therefore, the present paper compares the daily activity rhythm of the three Phodopus species under various conditions, from highly standardized laboratory to semi-natural ones. Motor activity was recorded by the mean of passive infrared sensors (PIR), running wheels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…For the present study, using both absolute and relative activity data complemented and verified each other. A higher activity during scotophase than during photophase has been described for rodents in general and has incidentally been shown for Djungarian hamsters ( Wynne-Edwards et al, 1999 ; Refinetti, 2006 ; Weinert et al, 2009 ), which could be confirmed in the present study ( Figures 8–10 , Table 3 , and Supplementary Table 6 ). Previously, different circadian phenotypes have been described, ranging from wild type over delayed onset and arrhythmic to non-responder ( Margraf et al, 1991 ; Gorman and Zucker, 1997 ; Schöttner et al, 2011 ).…”
Section: Discussionsupporting
confidence: 91%
“…For the present study, using both absolute and relative activity data complemented and verified each other. A higher activity during scotophase than during photophase has been described for rodents in general and has incidentally been shown for Djungarian hamsters ( Wynne-Edwards et al, 1999 ; Refinetti, 2006 ; Weinert et al, 2009 ), which could be confirmed in the present study ( Figures 8–10 , Table 3 , and Supplementary Table 6 ). Previously, different circadian phenotypes have been described, ranging from wild type over delayed onset and arrhythmic to non-responder ( Margraf et al, 1991 ; Gorman and Zucker, 1997 ; Schöttner et al, 2011 ).…”
Section: Discussionsupporting
confidence: 91%
“…Their activity patterns in the laboratory are consistent with wild behavior (Wynne‐Edwards et al. 1999; Weinert et al. 2009).…”
Section: Model Systemsupporting
confidence: 60%
“…As different mechanisms for magnetoreception in accordance with an animal's ecology and morphology have been proposed (Malkemper et al, 2015;Thalau et al, 2006), hamsters are of great interest, because both receptor mechanisms are equally probable. Hamsters possess well-developed eyes (Calderone & Jacobs, 1999), are nocturnal (Ross, 1994) but also active aboveground during twilight (Scheibler, Roschlau, & Brodbeck, 2014;Weinert et al, 2009), and the fact that the radical-pair mechanism is discussed to be usable also under starlight (Cochran, Mouritsen, & Wikelski, 2004) makes a radical-pair mechanism possible. In contrast, building extensive burrows (Gattermann et al, 2001) and living partly underground point to a magnetic particle-mediated mechanism.…”
mentioning
confidence: 99%